(untitled) (Latakia University Journal -Engineering Sciences Series, 2025)
Software-defined networking (SDN) architectures and applications have revolutionized the way wired networks are built and operated. However, their implementation in wireless environments still faces many obstacles. While we can implement centralized control in wired networks, wireless networks suffer from the difficulties of accessing and managing resources under centralized control. In reality, this is even more difficult in networks with constantly changing structures. Networks with changing architectures depend on diverse that differ in their structure, operation, and capabilities, including mobile devices of various types. At the same time, these networks need to provide flexibility in providing resources and services to end users. Since some links between end nodes are wireless in nature, unstable, and have a low rate. Reconnecting components to the controller and thus to each other, when these links are interrupted, especially when the path is multi-hop, will be difficult, if not impossible, because collecting the necessary statistical data to reconnect will be slow. This research seeks to use SDN to solve the problem of networks with changing architectures that are exposed to the possibility of frequent failure of network links. Given the increasing growth of the capabilities of the end devices and the network’s use of these capabilities provided by the end devices, the interest in spreading the functions of the network control plane at its edges, gives it a great potential to control and invest its resources better. In this context, a method has been proposed to make SDN more suitable for the environment of these networks by combining the central control of SDN and the distributed control that uses traditional protocols, in a hybrid design that takes the best of both models. That is, providing a general view of the network and the possibility of programming SDN on the one hand and using the robustness of traditional routing protocols on the other hand. Therefore, this research has been interested in proposing a mechanism for the operation of the hybrid node so that it can work as an SDN node or a traditional node, depending on the network condition and the availability of communication between its nodes. This takes into account the improvement of performance according to the parameters generally used in such cases.